Analisis Pengaruh Training, Pengembangan SDM Dan Motivasi Terhadap Produktivitas Kerja Pegawai di PT. Optimech Engineering Batam - Sabar Rismawati; Theresia Pradiani Pradiani; Fathorrahman (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of training, HR development, and motivation on employee work productivity at PT. Optimech Engineering Batam. This study used a quantitative approach with a population of 100 people. The sampling technique used a saturated sample. The data analysis technique used is multiple linear regression. The results showed that the training variable had a significant effect on employee work productivity at PT. Optimech Engineering is proven by the results of hypothesis testing where the t-count value is greater than the t-table value and the significant value is less than 0.05, the HR Development Variable has a significant effect on the Work Productivity of employees at PT. Optimech Engineering is proven by the results of hypothesis testing where the t-count value is greater than the t-table value and the significant value is less than 0.05. Furthermore, the motivational variable has a significant effect on the work productivity of employees at PT. Optimech Engineering is proven by the results of hypothesis testing where the t-count value is greater than the t-table value and the significant value is less than 0.05